Reversed Apico-Basal Myocardial Relaxation Sequence During Exercise in Long QT Syndrome Mutations Carriers With History of Previous Cardiac Events - Charisopoulou, Dafni; Koulaouzidis, George; Rydberg, Annika; Henein, Michael Y. (Frontiers in Physiology, 2022)
BACKGROUND: Recent echocardiography studies in inherited long QT syndrome (LQTS) have shown left ventricular (LV) myocardial relaxation disturbances to follow markedly prolonged and dispersed mechanical contraction. AIM: We used speckle-tracking echocardiography to assess disturbances in LV myocardial relaxation sequence during exercise and their relationship to symptoms. METHODS: Forty seven LQTS patients (45 ± 15 years, 25 female, 20 symptomatic, LVEF: 65 ± 6%) and 35 controls underwent exercise echocardiogram using Bruce protocol. ECG and echo parameters were recorded at rest, peak exercise (p.e.) and recovery. RESULTS: Between patients and controls there were no differences in age, gender, HR or LVEF. At p.e, patients had longer time to LV longitudinal ESR (tESR) at all three LV segments; basal (p<0.0001), mid- cavity (p= 0.03) and apical (p= 0.03) whereas at rest such difference was noted only at base (p=0.0007). Patients showed reversed apico-basal relaxation sequence (ΔtESRbase-apex) with early relaxation onset occurring later at base than at apex, both at rest (49 ± 43 vs. -29 ± 19msec, p<0.0001) and at p.e. (46 ± 38 vs. -40 ± 22mses, p<0.0001), particularly in symptomatic patients (69 ± 44 vs. 32 ± 26, p<0.0007). ΔtESRbase-apex correlated with longer QTc interval, lower ESR and attenuated LV stroke volume. CONCLUSIONS: LQTS patients show reversed longitudinal relaxation sequence, which worsens at exercise, particularly in those with previous cardiac events.